Analyzing Teachers’ Assessment Strategies in Teaching English - Lis a Isa; Enni Akhmad; Adimawati Helingo; Andi Nurwati; Jhems Richard Hasan (English Education Department, 2026)
This study aims to describe the classification of assessment strategies, implementation steps, and influencing factors in English language learning. Using a descriptive qualitative method, data were collected through interviews and observation with two English teachers. The results show the teacher A classifies strategies based on students’ interest through peer assessment and Kahoot, which are categorized as formative, informal, and authentic assessment. Teacher B classifies strategies based on students’ facility readiness through written tests via WhatsApp, categorized as summative and formal assessment. Teacher A implement 4 steps focusing on direct feedback, while teacher B applies 5 structured steps emphasizing vocabulary mastery. Influencing factors include time constraints that disrupt the feedback process, damage facilities such as speaker and projectors, and students’ low vocabulary mastery reduces answering speed and accuracy. Conclusion, the selection of assessment strategies is contextual and influencing by teacher pedagogical considerations and classroom conditions. Teachers are suggested to adjust strategies according to time, and students’ abilities.